Sustainable Practices and Innovations in Civil Engineering Select Proceedings of SPICE 2019 - Ramanagopal, S.; Gali, Madhavi Latha; Venkataraman, Kartik; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book presents the select proceedings of the International Conference on Sustainable Practices and Innovations in Civil Engineering (SPICE 2019). The chapters discuss emerging and current research in sustainability in different areas of civil engineering, which aim to provide solutions to sustainable development. The contents are broadly divided into the following six categories: (i) structural systems, (ii) environment and water resource systems, (iii) construction technologies, (iv)geotechnical systems, (v) innovative building materials, and (vi) transportation. This book will be of potential interest for students, researchers, and practitioners working in sustainable civil engineering related fields.
Studies on the Impact of Ternary Blend for Early Prediction of Compressive Strength Using Accelerated Curing -- Review Study on Glass Fibre Reinforced Gypsum (GFRG) Panels -- Modeling of Organic Acid Transport in Unsaturated Sub-Surface System -- State of the Art Review - Methods of Chromium Removal from Water and Waste -- Study on Behaviour of Web Stiffened Built-Up Beam -- Geotechnical Properties of gb (B-Glucan Treated Clayey Sand -- Composite Leaching of Thermal Power Plant Bottom Ash to Ensure Its Performance on Cement Mortar -- Enhancing the Performance of Bottom Ash using Acid Leaching Method -- An Experimental Investigation of Flexural Behaviour of Ferrocement Box Beams Using Micro Fillers -- An Analytical Framework of Climate Change Impacts on Water Resources: Vulnerability and Integrated Adaptation Strategies.s
Keywords: Engineering geology; Engineering$1 (BGeology.s; Foundations; Hydraulics; Sustainable architecture; Water pollution; Buildings$1 (BDesign and construction.s; Building; Construction; Engineering, Architectural; Transportation engineering; Traffic engineering; Geoengineering, Foundations, Hydraulics; Sustainable Architecture/Green Buildings; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Building Construction and Design; Transportation Technology and Traffic Engineering